1362 Early Experience on Flap Perfusion? Monitoring with Near-Infrared Spectroscopy Tissue Oximetry. (12th October 2021) - Hagiga, A; Ece Kumbasar, D; Dawood, O; Enrique Berner, J; Blackburn, A
Abstract: Introduction: Free flap reconstruction is a routine procedure with more than 99% success rates. Yet, vascular complications may occur leading to flap failure. Thus, early detection of vascular compromise is crucial for flap salvage. Vascular complications may be detected early using Infrared Spectroscopy Tissue Oximetry (NIRS) parameter changes. This method can distinguish changes caused by arterial and venous thrombosis before surgical re-exploration. This study aims to assess the validity or feasibility of using NIRS Oximetry in free flap monitoring and compare it to standard clinical examination and Doppler . Method: A prospective cohort observational study. Flap perfusion was measured using the INVOS™ 7100 system for 24-h continuous postoperative monitoring. The data were compared to findings of clinical assessment. Results: Ten patients completed the measurements after breast flap reconstruction. Age ranged from 41 to 61 years. Patients underwent immediate d eep inferior epigastric perforators (DIEP) (n = 4), delayed DIEP (n = 4), transverse upper gracilis flap (n = 1), and latissimus dorsi flap with lipofilling (n = 1). All ten flaps are successfully monitored for 24hrs post-operatively. The overall flap survival was 100%. Clinical examination, Doppler studies and surgical outcome were consistent with NIRS (need numbers). There were no false negatives. Conclusions: NIRS tissue oximetry could potentially monitor flaps non-invasively. Future adequately sampled cohort study is recommended.